Description of a new species and new records of Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from northern and northeastern Brazil - Paiva, Nathália De Oliveira; Rodrigues, Juliana Mourão Dos Santos; Franco, Cleilton Lima; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2023)
Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) is a species-rich and widespread genus of semiaquatic bugs, found both in freshwater and coastal marine environments. Despite the considerable number of species recorded from Brazil, the northern and northeastern regions of the country remain poorly explored. We present here the description of a new species of the angustipes complex, Rhagovelia leilae Paiva, Rodrigues & Moreira, sp. nov., and new records for the following species: R. brunae Magalhães & Moreira, 2016; R. evidis Bacon, 1948; R. hambletoni Drake & Harris, 1933; R. humboldti Polhemus, 1997; R. tenuipes Champion, 1898; and R. whitei (Breddin, 1898). These include the first records of species of Rhagovelia from the states of Pernambuco and Tocantins, and also increase the number of known species from the states of Alagoas, Bahia, and Maranhão to six, five and six, respectively.